Revitalization Technique Ecoprinting to Strengthening Education Character on Prospective School Teachers Base - Pratiwi, Indah; Amelia, Chairunnisa (Universitas Pendidikan Ganesha, 2025)
Developing creativity in the current era is essential, as creativity represents the outcome of new ways of thinking that support problem-solving skills. This study aims to examine the influence of the revitalization of the ecoprinting technique on strengthening character education among prospective elementary school teachers. The research employed a quasi-experimental design with a Non-Equivalent Group Design. The population consisted of all second-semester PGSD students, and the sample was determined using purposive sampling. The research instrument was an observation sheet validated by experts, yielding a score of 94%, indicating it was highly feasible. Data collection was carried out through participant observation, where the researcher was directly involved in field activities to observe how students’ character education developed through the application. The results showed a significant influence of the ecoprinting revitalization technique on strengthening character education in prospective teachers. This was evidenced by hypothesis testing, which produced a Sig. value of 0.000 < 0.05, leading to the rejection of the null hypothesis (H0) and the acceptance of the alternative hypothesis (Ha). Thus, the technique proved effective in reinforcing character education. In conclusion, this study contributes to generating new ideas for prospective teachers in creating educational media. Teachers are encouraged to develop learning media that promote active, creative, and character-building learning. The implication of this research is that students are given the opportunity to explore and develop their character through the media they create, while teachers act as facilitators who provide guidance and serve as role models.